IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN HASIL BELAJAR PJOK DI SEKOLAH MENENGAH PERTAMA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This review study aims to analyze the implementation of cooperative learning models in improving learning outcomes in Physical Education, Sports, and Health (PJOK) at the junior high school level. Data were collected from ten national studies published between 2022 and 2025 and analyzed using content analysis to identify patterns, effectiveness, and supporting or inhibiting factors. The findings show that cooperative learning models including STAD, TGT, Jigsaw, Think Pair Share, and Numbered Heads Together effectively enhance students’ cognitive, affective, and psychomotor learning outcomes. Cooperative learning promotes social interaction, collaboration, and motivation, creating a more active and inclusive learning environment. However, the success of this model depends on teachers’ classroom management skills and school facilities. Overall, cooperative learning models are recommended as an effective strategy for improving PJOK learning at the junior high school level.